Emerging narratives of parking supply and demand in contemporary cities. Issue Volume 14:Issues 1(2021) (2nd January 2021) - Pojani, Dorina; Sipe, Neil
ABSTRACT: Public views and perceptions surrounding parking demand and supply in Australian cities remain underexplored in the academic literature. In this exploratory study, we draw on written and oral qualitative data to set forth popular narratives and sentiments on parking supply and demand. We reveal two competing storylines. The first and more traditional one casts (free) parking as a "birthright" that is to be retained at all cost. The second and more recent storyline – which aligns closely to the position of contemporary planners – casts cars and parking as a "scourge" to be combated in order to restore urban liveability. We conclude that the emergence of this more recent storyline bodes well for the sustainability of urban areas.